Sequential organogenesis sets two parallel sensory lines in medaka - Seleit, Ali; Krämer, Isabel; Ambrosio, Elizabeth; Dross, Nicolas; Engel, Ulrike; Centanin, Lázaro (Development, 2017)
Animal organs are typically formed during embryogenesis by following one specific developmental programme. Here, we report that neuromast organs are generated by two distinct and sequential programmes that result in parallel sensory lines in medaka embryos. A ventral posterior lateral line (pLL) is composed of neuromasts deposited by collectively migrating cells whereas a midline pLL is formed by individually migrating cells. Despite the variable number of neuromasts among embryos, the sequential programmes that we describe here fix an invariable ratio between ventral and midline neuromasts. Mechanistically, we show that the formation of both types of neuromasts depends on the chemokine receptor genes cxcr4b and cxcr7b, illustrating how common molecules can mediate different morphogenetic processes. Altogether, we reveal a self-organising feature of the lateral line system that ensures a proper distribution of sensory organs along the body axis.